YOGURT KACANG MERAH PLUS SUSU KAMBING SEBAGAI SNACK SEHAT TINGGI ZAT BESI BAGI REMAJA ANEMIA - Sulistyaning, Afina Rachma; Putri, Widya Ayu Kurnia; Winarsi, Hery; Fitri, Armaida (GIZI INDONESIA, 2020)
The high prevalence of anemic adolescents in Indonesia resulted in urgent demand for a food product with high iron content as a healthy snack. This research aims to produce the best formula for red bean plus goat milk yogurt. The method was a randomized group design with two factors; the proportion of red bean and goat milk (100:0; 90:10; 80:20; 70:30), and fermentation time (12 and 24 hours). The organoleptic test includes flavor, smell, viscosity, color, and preference using a preference test with 55 panelists. Iron contents measured using the AAS method. The data were analyzed using ANOVA followed by Duncan?s Multiple Range Test. Organoleptic results analyzed using the Friedman test followed with a double comparative test. The best formula determined based on iron content and organoleptic results using the effectivity index. Red bean and goat milk proportion significantly affect iron content (p = 0.037). The combination of fermentation time and red bean-goat milk proportion significantly affects the sensory quality (p = 0.000). Fermentation time had no significant effect on iron content (p = 0.83). The iron contents were 23.30-33.62 mg/L. The best product has a red bean and goat milk proportion of 90 percent:10 percent, 24 hours fermentation, and 33.62 mg/ml iron content. The serving size is 80 ml, fulfilled 10.35 percent daily iron need of female adolescents.